INTENSITAS PEMBUKAAN WILAYAH HUTAN DAN EKSTRAKSI KAYU DALAM PENGUSAHAAN HUTAN ALAM DI LUARJAWA - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1991)
An investigation of forest infrastructure  and wood extraclion  intensilies was conducted in 10 logging componies in dry land forests and olver  10 logging companies in  swamp  forests outside Java from  1989  to 1991.For dry land forests, it is found that average  values of road density   (combined main and ranck roads) is 13 mlha, commercial  wood valume available for  harvesting is 56 cu.mlha,  and the realizalion of wood  extraclion  is 41 cu.mlha.  An  amount of commercial volume left unutilized in the forest (wood Waste) ir 15 cu.mlha.  While in swamp forats, lhose figures  are consecutively  11 mlha, 43 cu.mlha,  32.cu.mlha  and 11 cu.mllta. Staitstctllly, all the above valuts  of dry and swamp forests are   not significanly different.The above facts imply shat, nationwide, the high level of commercial  wood waste does occur. Our  estimale shows thet the figure could reach at least  3.7 million cu.m per year.efforts need to be done by all parties concmed to reduce shat waste to the  minimum level.